2020
DOI: 10.1177/0741932520924121
|View full text |Cite
|
Sign up to set email alerts
|

Special Educators’ Working Conditions, Self-Efficacy, and Practices Use With Students With Emotional/Behavioral Disorders

Abstract: Students with emotional/behavioral disorders (EBD) in self-contained settings depend on special educators to deliver high-quality instruction and behavior management, and special educators depend on administrators to create supportive working environments. Yet, to date, no studies have examined how working conditions relate to special educators’ provision of effective instructional or behavior management practices for students with EBD in self-contained settings. To fill this crucial gap, we conducted a nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 57 publications
(110 reference statements)
1
32
1
Order By: Relevance
“…Our findings suggest partners may play a key role in increasing workload manageability, by taking on other responsibilities so SETs can focus on instruction. Further, Cumming et al (2020) found no results for paraprofessional training, whereas our findings suggest potential complexities in relationships between paraprofessionals and instruction; consistency, number of parapro-fessionals, and time and support for training may all play a role. Consistent with their results, our findings tentatively support the importance of curricular resources, as Amelia's "hodgepodge" curricula may have contributed to disengaged and unfocused instruction.…”
Section: Findings Suggest Leaders Should Consider Investing In Personnel Tocontrasting
confidence: 88%
See 1 more Smart Citation
“…Our findings suggest partners may play a key role in increasing workload manageability, by taking on other responsibilities so SETs can focus on instruction. Further, Cumming et al (2020) found no results for paraprofessional training, whereas our findings suggest potential complexities in relationships between paraprofessionals and instruction; consistency, number of parapro-fessionals, and time and support for training may all play a role. Consistent with their results, our findings tentatively support the importance of curricular resources, as Amelia's "hodgepodge" curricula may have contributed to disengaged and unfocused instruction.…”
Section: Findings Suggest Leaders Should Consider Investing In Personnel Tocontrasting
confidence: 88%
“…Many studies have examined the working conditions SETs experience in self-contained settings for students with EBD (e.g., O'Brien et al, 2019), but to our knowledge, only one has examined how working conditions relate to these SETs' instruction. Cumming et al (2020) analyzed a national survey of SETs teaching students with EBD in self-contained classes. They found SETs who reported stronger curricular resources and more planning time were more likely to report using effective practices (e.g., praise).…”
Section: Working Conditions For Sets Serving Studentsmentioning
confidence: 99%
“…In addition to the role a teacher fulfills (special vs. general education), research using teacher self-report data indicates that instructional practices relate to feelings of burnout (Brouwers & Tomic, 2000;Cumming et al, 2020). Classroom management is one domain of instructional practice that is essential for teaching students who are at greater risk of exhibiting disruptive or challenging behavior in the classroom than their peers (Blackorby et al, 2005;Institute for Education Sciences, 2006;Newman et al, 2009;Reschly & Christenson, 2006; U.S. Department of Education Office for Civil Rights, 2014).…”
Section: Burnout and Classroom Managementmentioning
confidence: 99%
“…Both special and general education teachers may respond to burnout by making different career choices (Bettini, Cumming et al, 2020; Brunsting et al, 2014; Goddard & Goddard, 2006; Martin et al, 2012), feeling less able to do their work (Cumming et al, 2020; Hakanen et al, 2006; Skaalvik & Skaalvik, 2007), giving students less autonomy and choice (Shen et al, 2015), or changing their classroom management styles (Aloe, Shisler et al, 2014). Research suggests that student behavior may be the precursor to these associations; teachers develop burnout when faced with challenging behaviors from students (Aloe, Shisler et al, 2014; Skaalvik & Skaalvik, 2007).…”
Section: Burnout and Teachers Of Students With Ebdmentioning
confidence: 99%
See 1 more Smart Citation